Clinical evaluation of bonded brackets for three composite bonding systems - Hussain A Obaidi (University of Mosul, College of Dentistry, 2005)
Abstract Bonding the teeth with orthodontic brackets via orthodontic adhesive is essential stage in orthodontic treatment. But, still the failure bracket due to orthodontic or functional forces could be the predominant problem through the orthodontic treatment, in addition to the enamel fracture; in cases the bracket failed at the enamel-composite interface completely or partially (scores 0, 1, 2) as suggested by Artun and Bergland. This study is a clinically attempt to evaluate the failure- bracket number and the bracket failure sites, for three orthodontic composite systems, which were two paste (Concise); nomix (Right ON) and light cure (Transbond). These adhesives were used in bonding a stainless steel brackets to the teeth of adhesive system. The number of the failed brackets through 18 months of treatment were recorded and the site of the failed brackets were observed by magnifying lens (10×) and recorded according to the Artun and Bergland index. The results showed that there were no significant differences of failed brackets at p < 0.05 and 0.01 levels among these three composite systems, but the Concise adhesive had the least failure-brackets. The failure sites of the failed brackets for the three bonding systems were occurred at scores 2 and 3, while the Concise system had the highest percentage of score 3 site (80%) (composite bracket interface).